Social Vulnerability and Procedural Equity: Exploring the Distribution of Disaster Aid Across Counties in the United States. Issue 8 (November 2019) - Domingue, Simone J.; Emrich, Christopher T.
To date, there has been limited research conducted on disaster aid allocation across multiple regions and disasters within the United States. In addition, there is a paucity of research specifically connecting social indicators of vulnerability to public assistance grants aimed at restoring, rebuilding, and mitigating against future damages in disasters. Given these gaps, this article inquires as to whether the Federal Emergency Management Agency's (FEMA's) public assistance program is characterized by procedural inequities, or disparate outcomes for counties with more socially vulnerable populations. Specifically, this article analyzes county-level FEMA's Public Assistance distribution following major disaster declarations, while controlling for damages sustained, population, household counts, and FEMA Region. Results indicate that FEMA's Public Assistance program operates well when accounting only for disaster losses across the years, however, findings also show that county social conditions influence funding receipt. Although socioeconomic characteristics were significant drivers of assistance spending, additional vulnerability indicators related to county demographic and built environment characteristics were also important drivers of receipt. Cases of both procedural inequity and equity are highlighted, and implications for equitable disaster recovery are discussed along with recommendations.